First-year implementation of mailed FIT colorectal cancer screening programs in two Medicaid/Medicare health insurance plans: qualitative learnings from health plan quality improvement staff and leaders - Laura-Mae Baldwin; Jennifer L. Schneider; Malaika Schwartz; Jennifer S. Rivelli; Beverly B. Green; Amanda F. Petrik; Gloria D. Coronado (BMC, 2020)
Abstract Background Colorectal cancer screening rates remain low, especially among certain racial and ethnic groups and the uninsured and Medicaid insured. Clinics and health care systems have adopted population-based mailed fecal immunochemical testing (FIT) programs to increase screening, and now health insurance plans are beginning to implement mailed FIT programs. We report on challenges to and successes of mailed FIT programs during their first year of implementation in two health plans serving Medicaid and dual eligible Medicaid/Medicare enrollees. Methods This qualitative descriptive study gathered data through in-depth interviews with staff and leaders at each health plan (n = 10). The Consolidated Framework for Implementation Research, field notes from program planning meetings between the research team and the health plans, and internal research team debriefs informed interview guide development. Qualitative research staff used Atlas.ti to code the health plan interviews and develop summary themes through an iterative content analysis approach. Results We identified first-year implementation challenges in five thematic areas: 1) program design, 2) vendor experience, 3) engagement/communication, 4) reaction/satisfaction of stakeholders, and 5) processing/returning of mailed kits. Commonly experienced challenges by both health plans related to the time-consuming nature of the programs to set up, and complexities and delays in working with vendors. We found implementation successes in the same five thematic areas as well as four additional areas of: 1) leadership support, 2) compatibility with the health plan, 3) broader impacts, and 4) collaboration with researchers. Commonly experienced successes included the ability to adapt the mailed FIT program to the individual health plan culture and needs, and the synchronicity between the programs and their organizational missions and goals. Conclusions Both health plans successfully adapted mailed FIT programs to their own culture and resources and used their strong quality management resources to maximize success in overcoming the time demands of setting up the program and working with their vendors. Mailed FIT programs administered by health plans, especially those serving Medicaid- and dual eligible Medicaid/Medicare-insured populations, may be an important resource to support closing gaps in colorectal cancer screening among traditionally underserved populations.